THE ROLE OF MONOLOGUE AND DIALOGUE IN THE PROCESS OF TEACHING STATE LANGUAGE TO PRIMARY CLASS STUDENTS IN SCHOOLS IN UZBEKISTAN THAT CONDUCT EDUCATION IN THE TAJIK LANGUAGE (Scientific journal of the Fergana State University, 2024)
This article analyzes the role of monologue and dialogue in the process of teaching the state language to primary school students in schools with Tajik as the medium of instruction in Uzbekistan. The theoretical foundations of dialogic and monologic speech, as well as the pedagogical views of Uzbek and foreign scholars, are presented. The article discusses the importance of monologic and dialogic speech in the development of independent and creative thinking in primary school students. Additionally, it highlights the significance of exercises that contribute to the formation of dialogic and monologic speech in students. The research results offer effective methods and practical recommendations for developing oral speech in primary school students. This article will be useful for educators and specialists in the field of education, as it demonstrates the importance of monologue and dialogue in the process of teaching the state language. The study employs methods of theoretical analysis, comparative analysis, and practical analysis. Through theoretical analysis, the foundations of dialogic and monologic speech and pedagogical views are studied. Comparative analysis is used to examine the unique characteristics of monologue and dialogue in various languages and cultural contexts. Practical analysis involves the examination of exercises aimed at developing dialogic and monologic speech in students and assessing their effectiveness. The research results offer effective methods and practical recommendations for developing dialogic and monologic speech. It is shown that these methods are important for the formation of students' social and cultural skills.